Hubungan Pola Asuh Orangtua dengan Perilaku Seksual Remaja dalam Berpacaran - Chandi Salmon Conrad; Sarlito Wirawan Sarwono (Jurnal Ilmiah Psikologi MIND SET, 2010)
The study aimed to examine the correlation between parenting styles with adolescent's sexual behavior. There were 274 respondents participated in this study, ranging from 14 to 22 of age. The underlying theories used in this study were four parenting styles developed by Baumrid: authoritative, authoritarian, permissive and uninvolved, and four types of sexual behavior set up by Duval and Miller: touching, kissing, petting, and intercourse. The result which was based on chi square computation yielded a value 12.040 (p<0.05) which meant that there was no significant correlation between parenting style and adolescent's sexual behavior. Some aspects of theory, methodology and samplings which were used in the study and contributed to the result were also analyzed.